Development engineering : empowering the poor through sustainable technology-based solutions - Kisaalita, William Ssempa, 1953- (Cambridge Scholars Publisher, 2020)
This book details the development and evaluation of technological interventions designed to improve human and economic development within complex, low-resource settings, showing that a solution becomes an innovation when it reaches widespread use. The book shortens the time-gap between development and up-take of the intervention, especially for student solution-developers or innovators who are new to the cultural and geopolitical settings of the problem-source country or region. Technological interventions in development are sustainable if they meet a real need, are affordable by the users, fi.